Medicinal species from Brazil with anti-inflammatory or antioxidant potential: A review (Research, Society and Development, 2021)
Medicinal plants have been used by the population since time immemorial, representing a remarkable source for the treatment of various human diseases, that may have their risk reduced by eating products based on these plants, benefits are attributed to some secondary metabolites that have an anti-inflammatory and/or antioxidant activity. The aim of this study is to perform a literature searching for the most commonly used species of medicinal plants in Brazil with anti-inflammatory and antioxidant potential of the last decade. Were used publications indexed in the databases: PubMed, Science Direct and Scielo in the last 10 years, using the following descriptors: “Brazilian medicinal plants”, “anti-inflammatory activity” and “antioxidant activity” Using the Boolean marker “AND” ensuring specificity in searches. 1,185 articles were identified, 1.140 were eliminated because they did not meet the inclusion or exclusion criteria. A total of 45 articles published were included, which were categorized according to the use for anti-inflammatory and antioxidant activity. Among the active compounds with anti-inflammatory activities there are some polyphenolic compounds, in addition to alkaloid, terpenoid and steroid. These secondary metabolites act on different targets involved in the inflammatory process. Studies have shown that polyphenolic compounds, especially flavonoids, have bioactive compounds with antioxidant properties that can be used for therapeutic purposes in diseases such as chronic degenerative diseases. These results suggest the prospects for future studies to obtain a better understanding of the individual components and the use of these compounds as a possible therapeutic agent for pathologies such as inflammation and free radicals.